2015
DOI: 10.1002/agr.21436
|View full text |Cite
|
Sign up to set email alerts
|

Detecting COOL Impacts on United States–Canada Bilateral Hog and Pork Trade Flows

Abstract: This paper examines the impact of mandatory Country of Origin Labeling on American imports of Canadian hogs and pork by testing for structural change. Given the uncertainties over the timing of the implementation and reform of COOL, we implement statistical procedures that endogenously test for structural change over multiple time periods. We find evidence that COOL has impacted U.S./Canada feeder and slaughter hog trade flows. In contrast, we found no evidence of structural change for pork trade flows that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Twine et al (2016) find that the implementation of COOL acted as a structural change in U.S. imports of both feeder and fed cattle from Canada. Additionally, Rude et al (2016) assert that COOL caused structural change in the market for U.S. hog imports from Canada; however, these authors find no evidence of structural change in pork imports from Canada resulting from COOL implementation. COOL-related analyses have considered other industries as well: Johnecheck et al (2010) found that the implementation of COOL may potentially reduce the value of Mexican tomato exports to the United States by 14% to 32% and may result in modest U.S. consumer welfare increases compared to the increased (decreased) surplus of domestic (Mexican) tomato producers.…”
mentioning
confidence: 94%
“…Twine et al (2016) find that the implementation of COOL acted as a structural change in U.S. imports of both feeder and fed cattle from Canada. Additionally, Rude et al (2016) assert that COOL caused structural change in the market for U.S. hog imports from Canada; however, these authors find no evidence of structural change in pork imports from Canada resulting from COOL implementation. COOL-related analyses have considered other industries as well: Johnecheck et al (2010) found that the implementation of COOL may potentially reduce the value of Mexican tomato exports to the United States by 14% to 32% and may result in modest U.S. consumer welfare increases compared to the increased (decreased) surplus of domestic (Mexican) tomato producers.…”
mentioning
confidence: 94%